Answer: The solution is [2, 1]
Step-by-step explanation:
The given system of simultaneous equations is expressed as
7x - 6y = - 20 - - - - - - - - - - 1
3x + 5y = - 1 - - - - - - - - - - - - -2
We would eliminate x by multiplying equation 1 by 3 and equation 2 by 7. It becomes
21x - 18y = - 60 - - - - - - - - - - 3
21x + 35y = - 7 - - - - - - - - - - 4
Subtracting equation 4 from equation 3, it becomes
- 53y = - 53
Dividing the left hand side and the right hand side of the equation by - 53, it becomes
- 53y/ - 53 = - 53/ - 53
y = 1
Substituting y = 1 into equation 2, it becomes
3x + 5 × 1 = - 1
3x + 5 = - 1
Subtracting 5 from the left hand side and the right hand side of the equation, it becomes
3x + 5 - 5 = - 1 - 5
3x = - 6
Dividing the left hand side and the right hand side of the equation by 3, it becomes
3x/3 = - 6/3
x = 2